Foreign language learning strategies of three Indonesian multilinguals: A narrative inquiry study - Mardiana, Rizdika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Foreign language learners usually learn a foreign language using their first language. There has been limited report on study discussing the ability of foreign language learners to learn a foreign language using their learned foreign language. This study employed an autobiographical narrative inquiry based on the experience of three multilinguals. This study aimed to find out their strategies in learning foreign languages and the factors affecting in learning foreign languages. This study found that there were two Indonesian multilinguals that learn Japanese using their limited ability in English. The other multilingual learn English at school and learned Dutch at a language course. The results proved that there are factors such as learner characteristics, linguistic factors, learning processes, age and acquisition, instructional variables, context, purpose, motivation, attention, attitude, study habit, self-concept, and student aptitude affecting learners in learning foreign languages. This study gives little contribution to our understanding on the strategies that might been applied by a foreign language learner to learn a new foreign language.